2021
DOI: 10.1186/s12981-021-00416-1
|View full text |Cite|
|
Sign up to set email alerts
|

Adverse events of inactivated COVID-19 vaccine in HIV-infected adults

Abstract: This study aims to evaluate the safety of inactivated COVID-19 vaccine among adult people living with HIV (PLWH). In total, 259 PLWH who received at least one dose of inactivated COVID-19 vaccine were enrolled, and post-vaccination adverse events (AEs) were evaluated seven days following each vaccination dose. The overall AE frequency was 22.8% after dose one, which was higher than after dose two (10.2%) (P < 0.001). No severe side event or vaccine safety concern was observed. Our finding was essential in r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 6 publications
3
23
0
Order By: Relevance
“…Similar results were also found in inactivated COVID-19 vaccine ( 10 ). Our former study also showed no serious adverse events for COVID-19 vaccination were observed among PLWH in China ( 11 ). Above evidence had proved that PLWH could benefit from COVID-19 vaccination.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Similar results were also found in inactivated COVID-19 vaccine ( 10 ). Our former study also showed no serious adverse events for COVID-19 vaccination were observed among PLWH in China ( 11 ). Above evidence had proved that PLWH could benefit from COVID-19 vaccination.…”
Section: Introductionmentioning
confidence: 69%
“…The national technical guideline for COVID-19 vaccination in China encourages PLWH to take up inactivated vaccines or recombinant subunit vaccines ( 38 ). Several studies have reported that the PLWH has a comparable immune response to COVID-19 vaccines and there are no serious adverse events after COVID-19 vaccination ( 11 , 39 ). It is essential to design and develop health education programs to improve their perceptions and confidence in COVID-19 vaccines to improve COVID-19 vaccination coverage.…”
Section: Discussionmentioning
confidence: 98%
“…Our current knowledge on COVID-19 vaccination in PLWHA was based on the findings from trials involving stable HIV patients that suggest the safety, tolerability, and immunogenicity of COVID-19 vaccines [ 5 8 ]. This is also emphasized by the recommendations of the WHO and CDC for COVID-19 vacci-nation in PLWHA [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies reported that inactivated COVID-19 vaccine showed safety in PLWHA who received ART but a poor immunological response was observed in those with CD4+ count <350 cells/µl [ 7 ]. Furthermore, there are also no data reporting that these COVID-19 vaccines are inefficacious and unsafe or interfere with ART [ 5 8 ]. Here, we report 2 cases of young men with previously unknown HIV status whose neurological symptoms emerged and worsened progressively after receiving the first dose of vaccine against SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%
“…These studies comprised one cross-sectional study, 16 one case-control study 17 and 20 cohort studies 12,13,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] (15 prospective cohort studies, 13,[18][19][20][21][22][23][24][25][26][27]29,31,32,35 three retrospective cohort studies 12,28,34 and one nonrandomized cohort study 33 ). These 22 studies were conducted in different regions, including Asia, 13,[16][17][18]21,23,32,33,35 Europe, 12,…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%